2016
DOI: 10.1177/0301006616679172
|View full text |Cite
|
Sign up to set email alerts
|

The Independent Perceptual Calibration of Action-Neutral and -Referential Environmental Properties

Abstract: Two experiments were conducted to explore how the calibration of perception of environmental properties taken with reference to an animal and their action capabilities (e.g., affordances) and those that are independent of action capabilities (e.g., metric properties) relate. In both experiments, participants provided reports of the maximum height they could reach above their head with a number of different stick(s) (reach-with-stick height) and the length of those stick(s), a property that is a constituent of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 54 publications
0
18
0
Order By: Relevance
“…That children's abilities develop differently in each task lends further support to the action-specific account of perception as opposed to the action-general account. Future research could address this question more directly by testing whether children's perceptual judgments of an object that modifies affordances (platform shoes or backpacks) is related to their perception of affordances, replicating the strategies used in adult studies (Mark, 1987;Thomas et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…That children's abilities develop differently in each task lends further support to the action-specific account of perception as opposed to the action-general account. Future research could address this question more directly by testing whether children's perceptual judgments of an object that modifies affordances (platform shoes or backpacks) is related to their perception of affordances, replicating the strategies used in adult studies (Mark, 1987;Thomas et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence supports this claim: Mark (1987) demonstrated that observers' perception of affordances for sitting while wearing platform shoes was independent of their perception of the size of the platform shoes. This implies that observers recalibrate by learning something intrinsic about the body's abilities relative to the environment rather than by computing an affordance from constituent properties (see also Thomas, Wagman, Hawkins, Havens, & Riley, 2016). Thus, recalibration is not as simple as "adding" the perceived size of the platform shoe to adjust one's judgment of sitting or the perceived size of a backpack to one's judgment of fitting through doorways.…”
mentioning
confidence: 99%
“…Thus, it is unknown whether participants could have recalibrated without vision of the body-modifying object or whether visual access conferred any advantage. I predict that vision of the body-modifying object is not critical: Past work shows that affordance perception is independent of judgments of objects that alter affordances (Mark, 1987;Thomas & Riley, 2014;Thomas et al, 2016). Moreover, participants were no worse at judging affordances for reaching with rods when rods were present in view or absent (Thomas & Riley, 2014).…”
Section: Recalibration and Exploration In Affordances For Fittingmentioning
confidence: 93%
“…Seeing the backpack may have also helped participants in the PF condition make slightly more accurate judgments during pretest trials. Finding a benefit of vision of the backpack was unexpected given that past work demonstrated perceptual independence between affordance judgments and metric judgments of objects that manipulated affordances (Mark, 1987;Thomas & Riley, 2014;Thomas et al, 2016). However, these benefits of visual information about the backpack should be interpreted cautiously because differences between vision conditions were only observed when measuring accuracy as a proportion of manipulation size.…”
Section: Vision Of the Backpackmentioning
confidence: 99%
See 1 more Smart Citation